Exploring DNA degradation in situ and in museum storage through genomics and metagenomics - Anne Marie Høier Eriksen; Juan Antonio Rodríguez; Frederik Seersholm; Hege Ingjerd Hollund; Anne Birgitte Gotfredsen; Matthew James Collins; Bjarne Grønnow; Mikkel Winther Pedersen; M. Thomas P. Gilbert; Henning Matthiesen (Communications Biology)
Abstract Understanding the environmental and microbial processes involved in DNA degradation from archaeological remains is a fundamental part of managing bone specimens. We investigated the state of DNA preservation in 33 archaeozoological caribou (Rangifer tarandus) ribs excavated from the same excavation trench at a former Inuit hunting camp in West Greenland, separated by 43 years: 1978 and 2021. Our findings show that DNA is better preserved in the most recently excavated samples, indicating a detrimental effect of museum storage on DNA integrity. Additionally, our data reveals a diverse microbiome in these bones, encoding genes relevant for bone degradation, such as enzymatic families relating to collagenases, peptidases and glycosidases. Microbes associated with bone degradation were present in both new and historical samples, with museum-stored bones showing significantly more DNA damage. Overall, our research sheds light on the nuanced dynamics governing the preservation of genomic material in archaeological contexts, underscoring the vital importance of careful considerations in museum curation practices for the sustainable conservation of invaluable skeletal records in museum repositories and in situ.